Assessment by HPLC of the degradation behavior of acitretin under hydrolytic, oxidative, photolytic and thermal stress conditions - Pawan K. Porwal; Neeraj Upmanyu (Elsevier, 2014)
Acitretin is a photosensitive oral retinoid with very limited data available on its degradation. The official HPLC method for acitretin determination was insufficient to resolve the degradation products generated during stability studies. Therefore, an isocratic RP-HPLC-UV method was developed for the determination of acitretin in the presence of its related impurities and degradation products. Efficient chromatographic separation was achieved on a Thermo beta-basic column C18 (100 mm×4.6 mm, 5 μm) with mobile phase containing 0.3% (v/v) glacial acetic acid with acetonitrile (ACN) and isopropyl alcohol (IPA) in an isocratic ratio of 70:30 at a flow rate of 1.0 mL/min with the eluent monitored at 360 nm. The method was validated for specificity, linearity, precision, accuracy and robustness. The calibration plot was linear over the concentration range of 50-150 μg/mL with a correlation coefficient (r2) of 0.999. The proposed method was used to investigate the degradation kinetics of acitretin under the different degradative conditions. The degradation rate constant (K), half-life (t1/2), and t90 were calculated. Degradation of acitretin followed pseudo-first-order kinetics. The drug was found to be less stable under acidic and photolytic degradation conditions: the photolytic degradation constants for acitretin in sunlight and UV light were 0.002698% and 0.0008402% min−1, respectively. The LOD for acitretin and the known impurities were at a level below 0.02%. The method shows consistent recoveries for ACTR (99.8%-101.2%) and also for its known impurities (97.2-101.3%). The method was found to be accurate, precise, linear, specific, sensitive, rugged, robust, and useful for characterizing the stability of this chemical.